Automated bicycle crash detection system - Anuar, Muhammad Zahirulhaq Zainol; Zambri, Nor Aira; Salim, Norhafiz; Yi, Sim Sy; Hassan, Omar Abu (2023)
Road accidents rate are now very high, especially for two-wheeled vehicle. It is necessary to have a sort of road accident detection and information system to rescue the injured victims. This research aims to create a prototype of an ABCDs that is implemented at a bicycle. The main target is to minimize the accident’s response time whenever accident occurs. The accident detection uses the ESP8266 Node MCU, smartphones, GSM and GPS technology, AXL 335 accelerometer and Blynk for mobile applications. The input is an accelerometer that detects the shock and Node MCU will send the location via Email or mobile phone. The GPS receiver module detects geographical coordinates of the area and signal message will be sent through GSM. To validate the prototype, three separated tests were conducted andthe test was performed for various type of open area, closed area, with different fixed value test as well. Testing data shows that the prototype successfully detected crash or accident and notification was successfully delivered through Blynk. Inevitably, this project help in providing assistance for the accident victims in emergency situations within short period of time. Indeed, with a proper setup and adjustment, this prototype benefits riders in helping everyone’s helps lives because life was a blessing for everybody,